Pediatric emergency radiology - Dietrich, Ann M.; Sreedher, Gayathri (New York, NY : Oxford University Press, 2023)
An engaging collection of thought-provoking cases which clinicians can utilize for effective imaging of pediatric patients in emergency situations.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 3, 2023).
Keywords: Pediatric emergencies; Pediatric radiology; Health and Wellbeing; Clinical & internal medicine